Nanofiltration membrane from chitosan-latex - Muhd Nashriq, Aziz (Ministry of Education, Thailand, 2013)
Muhd Nashriq Aziz and his partner has participated in 8th International Exhibition for Young Inventors (IEYI 2012), 28th - 30th June 2012 held at Bangkok International Trade and Exhibition Centre (BITEC), Bangkok, Thailand.